MINERAL NUTRIENT COMPOSITIONS OF FIELD-GROWN WEED AND MAIZE (Zea mays L.) PLANTS IN TERMS OF COMPETITION - (:unkn) unknown (University of Agriculture, 2021)
The unplanned development of cities creates several problems like deterioration of environment, unbalanced ecosystem and poor community interrelation. Furthermore, shifting rural communities to urban areas can damage the urban forestry by conversion of natural habitat into concrete heat island. In this scenario, for improvement of urban environmental quality, people’s perception and opinion could be helpful for better implementation of urban management decisions. The objectives of this study were to examine the perception of urban dwellers towards urban trees and to explore the variation in opinion for managing the diverse types of urban spaces. The present study was conducted in 3rd most populous city of Pakistan viz. Faisalabad, divided into four categories i.e. parks, hospitals, institutions, and urban communities. A questionnaire-based survey was conducted by four hundred respondents with a hundred from each category to analyze people’s perception, attitude, and preference towards urban trees. Results depicted diversity among respondents related to age, education, profession, and monthly income. Three most abundant tree species in Faisalabad named Eucalyptus camaldulensis Dehnh. (17%), Conocarpus erectus L. (43%) and Vachellia nilotica (L.) P. Hurter & Mabb. (12%) were disliked due to various problems like accidents, garbage, sewerage problems, and electric transmission issue, respectively. Moreover, it was also assessed that demographic characters i.e. gender, age, education, income, and profession have a strong association on liking and disliking of urban trees. This study helps to analyze the people’s perception, attitude, and preference towards urban vegetation and provide valuable information for establishing future green belts. © 2021, University of Agriculture. All rights reserved.
Keywords: Afforestation; Parks; Tree planting; Urban landscape; Urban sustainability